Microstructure and dielectric properties of Ag-BaTiO3 composite ceramics. Issue 16 (December 2018) - Turcan, Ina; Lukacs, Vlad Alexandru; Curecheriu, Lavinia; Padurariu, Leontin; Ciomaga, Cristina Elena; Airimioaei, Mirela; Stoian, George; Lupu, Nicoleta; Mitoseriu, Liliana
Abstract: Di-phase composite ceramics based on BaTiO3 with 5 vol% of Ag filler have been prepared by sintering the mixture of powders at temperatures above the silver melting point (1000 °C–1300 °C/2 h). As predicted by finite element calculations, the addition of metallic particles should produce a field concentration in some regions of the BaTiO3 matrix and therefore, an enhanced dielectric response with respect to pure BaTiO3 . The role of oxygen vacancies on the dielectric relaxation mechanisms of Ag-BaTiO3 composites has been investigated. The sintering temperature of 1200 °C provided optimized ceramics with excellent dielectric properties, i.e. with low losses (tanδ < 3%) and room temperature permittivity measured at 50 kHz exceeding 6500 (and above 13, 000 at the Curie temperature), as result of a good densification (94% relative density) and a synergy effect of the metallic particles inclusions and ceramic grain size in the range of ≈1 μm, where BaTiO3 has a well-known maximum of its permittivity.